Performance of cowpea (Vigna unguiculata) under mandarin based agroforestry systems in Vidarbha region of Maharashtra - Deshmukh, Aarti P.; Singh, Lalji; Ilorkar, V.M. (Indian Journal of Agroforestry, 2021)
Traditional agroforestry is very common in Vidarbha region of Maharashtra with tree species. Now fruit tree crops are also introduced in farm land to increase the farmerâ€™s income. Hence, the experiment was conducted at AICRP on Agroforestry research farm at College of Agriculture, Nagpur, Maharashtra under citrus (mandarin) based agroforestry systems. The citrus fruit trees were planted at a distance of 6 Ã— 6 m and tree species including Tectona grandis, Eucalyptus tereticornis and Ailanthus excelsa were planted during 2015-16 at equilateral distance of 3 m in each treatment between two mandarin trees, where, cowpea crop (Vigna unguiculata var. Gomati) was cultivated as intercrop under the traditional agri-horti-silviculture system during 2020-21. The growth performance and yield of cowpea under different set of treatments viz., T1 (sole cowpea), T2 (sole Mandarin + cowpea), T3 (mandarin + T. grandis + cowpea), T4 (mandarin + E. tereticornis + cowpea) and T5 (mandarin + A. excelsa + cowpea) were recorded. The growth parameter and yield of cowpea crop was found maximum in open field (sole cowpea) than the treatments under citrus based agroforestry systems and it was 25.57, 56.35, 44.00 and 63.12% higher as compared to T2, T3, T4 and T5, respectively. The grain and straw yield of cowpea was 0.57 and 1.13 t ha-1in crop of open field (sole cowpea). As regard the soil fertility, the most important parameter i.e. the organic carbon was significantly increased in sole cropping (0.57), sole mandarin (0.53) and mandarin + A. excelsa (0.48). Whereas, it was decreased under mandarin + T. grandis (0.48) and mandarin + E. tereticornis (0.44) after the harvesting of kharif cowpea crop.